Autentikasi Hadis-Hadis Kitab Jinayah Dan Hudud Daripada Kitab Bulughul Maram Karya Al-Hafiz Ibn Hajar Al-Asqalani - Mohd Muhiden Abd Rahman; Shukriah Binti Che Kassim; Thuraya Mohd Said @ Hashim (USIM Press, 2024)
Vol 7. No. 2 Page (18-34)